2022
DOI: 10.3389/fnins.2022.823423
|View full text |Cite
|
Sign up to set email alerts
|

An Anodic Phase Can Facilitate Rather Than Weaken a Cathodic Phase to Activate Neurons in Biphasic-Pulse Axonal Stimulations

Abstract: Electrical pulses have been promisingly utilized in neural stimulations to treat various diseases. Usually, charge-balanced biphasic pulses are applied in the clinic to eliminate the possible side effects caused by charge accumulations. Because of its reversal action to the preceding cathodic phase, the subsequent anodic phase has been commonly considered to lower the activation efficiency of biphasic pulses. However, an anodic pulse itself can also activate axons with its “virtual cathode” effect. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
2
1
0
Order By: Relevance
“…The above experimental results and our previous study (Feng et al 2022) have shown that the A-HFS ⊤⊥ -induced suppression of the neuronal activations must have generated at the axons instead of the somata. Otherwise, the somata would not have distinguished the APs induced initially on axons by the two types of pulses and made distinct suppressions of APS ⊤ and APS ⊥ .…”
Section: Generation-failure and Conduction-failure Of Aps In The Axon...supporting
confidence: 71%
See 2 more Smart Citations
“…The above experimental results and our previous study (Feng et al 2022) have shown that the A-HFS ⊤⊥ -induced suppression of the neuronal activations must have generated at the axons instead of the somata. Otherwise, the somata would not have distinguished the APs induced initially on axons by the two types of pulses and made distinct suppressions of APS ⊤ and APS ⊥ .…”
Section: Generation-failure and Conduction-failure Of Aps In The Axon...supporting
confidence: 71%
“…The experimental results presented here and in our previous studies (Feng et al 2013(Feng et al , 2022 have shown that the HFS-induced suppressions of neuronal activations mainly occur at axons instead of somata. Therefore, to focus on the investigation of axonal mechanisms, here we utilized an axonal model without other neuronal elements such as axonal initial segment, soma and dendrites.…”
Section: Limitationssupporting
confidence: 70%
See 1 more Smart Citation